Penerapan Pembelajaran Berbasis SDGs untuk Meningkatkan Kualitas Pendidikan Dasar yang Inklusif dan Berkelanjutan - Septiana, Nanda; Firdausi, Rofiqoh (Prodi PGMI STAI Al-Akbar Surabaya, 2025)
Primary education plays a crucial role in shaping a generation that is prepared to face global challenges, one of which is through the implementation of the Sustainable Development Goals (SDGs). This study aims to analyze the role of SDG-based learning innovations in improving the quality of primary education in Indonesia, with a focus on sustainable learning that is accessible to all segments of society. In addition, the study also identifies the challenges and strategies faced by educators in implementing SDG-based learning innovations in elementary schools. The method used is a literature review by examining various journals, books, and reports related to the implementation of SDGs in primary education. The results of the study indicate that SDG-based learning innovations, particularly through Project-Based Learning (PjBL), can enhance students’ social and academic skills, yet still face challenges in terms of limited resources and teacher training. Therefore, further efforts are needed to provide adequate infrastructure and training for educators.